Controllable synthesis of graphene supported MnO2 nanowires via self-assembly for enhanced water oxidation in both alkaline and neutral solutions - Yuan, Weiyong; Shen, P.; Jiang, San Ping (R S C Publications, 2013)
The sluggish water oxidation reaction represents a significant challenge in water splitting for energy storage using hydrogen. We herein report the synthesis of MnO2 nanowires with the ultrasmall diameter and aspect ratio as high as 125 on graphene using a novel in situ polymer-mediated self-assembly approach in aqueous solution and under ambient conditions. The self-assembly process is simple and controllable by the concentration and pH of the polymer solution, in which the polymer serves as a soft template to direct the growth of MnO2 nanowires and also stabilize the structure, forming a unique graphene supported MnO2 nanowire, G@MnO2 NW. This nanostructure shows the most significant improvement of the catalytic activity compared to the graphene supported MnO2 nanoparticle and commercial Pt/C toward water oxidation under both alkaline and neutral conditions, and demonstrates for the first time a remarkable effect of the shape of MnO2 nanostructures on water oxidation catalysis. For example, at 0.7 V, it produces a current density of 5.9 mA cm−2, 14.8 times that of the graphene supported MnO2 nanoparticle (4.0 mA cm−2) and 8.4 times that of Pt/C (0.7 mA cm−2) in alkaline solution. Furthermore, it displays the highest turnover frequency reported among all the Mn oxides used for water oxidation catalysis. The G@MnO2 NW shows great potential as a water oxidation catalyst for energy storage applications.